Tetraspanins - Rubinstein, Eric; Berditchevski, Fedor (Proteins and Cell Regulation, 2013)
Tetraspanin proteins have recently emerged as a new class of modulators of various processes involving cell surface receptors, including cell migration and invasion, host immune responses, cell-cell fusion, and viral infection. The book summarises recent advances in the fields of biology in which the role of tetraspanins have been established and also covers the molecular evolution of the tetraspanin superfamily and structural aspects of the organisation of tetraspanin microdomains.